1989
DOI: 10.2216/i0031-8884-28-2-222.1
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar autofluorescence in forty-four chlorophyll c-containing algae

Abstract: A survey of flagellar autofluorescence was made in 44 species of chlorophyll c-containing algae. In the five species of Chrysophyceae examined, flagellar autofluorescence was observed throughout the length of the short smooth flagellum, but only when this was associated with an eyespot and a flagellar swelling. In the three species of Synurophyceae, which lack an eyespot and have swellings in both flagella, the fluorescence was also observed in the short smooth flagellum. Among the Xanthophyceae, Botrydiopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Eyespots are part of the photoreceptor apparatus (also called the eyespot apparatus), shielding light so that the other elements can more precisely determine the direction of light (Foster and Smyth, 1980). In a wide variety of heterokont and haptophyte algae, one flagellum possesses an autofluorescent substance (flavin and pterin-like in brown algae) that plays a role in phototaxis (Müller et al, 1987;Kawai and Inouye, 1989;Kawai et al, 1996). In the typical case (most heterokont algae, Pavlovophyceae), the eyespot lies just inside the chloroplast in the area immediately adjacent to the mature flagellum.…”
Section: Cell Biology-chloroplasts and Their Pigments-mentioning
confidence: 99%
“…Eyespots are part of the photoreceptor apparatus (also called the eyespot apparatus), shielding light so that the other elements can more precisely determine the direction of light (Foster and Smyth, 1980). In a wide variety of heterokont and haptophyte algae, one flagellum possesses an autofluorescent substance (flavin and pterin-like in brown algae) that plays a role in phototaxis (Müller et al, 1987;Kawai and Inouye, 1989;Kawai et al, 1996). In the typical case (most heterokont algae, Pavlovophyceae), the eyespot lies just inside the chloroplast in the area immediately adjacent to the mature flagellum.…”
Section: Cell Biology-chloroplasts and Their Pigments-mentioning
confidence: 99%
“…Several authors have reported the presence of a flavin-like autofluorescent substance in the posterior smooth flagellum of phototactic flagellated cells of brown algae; the anterior flagellum or the stigma showed no autofluorescence (Miiller et al 1987;Kawai 1988). Such autofluorescence has also been observed in the smooth flagellum of some related chlorophyll-c-containing algae (Mfiller et al 1987;Coleman 1988;Kawai 1988;Kawai and Inouye 1989). Kawai et al (1990) studied the action spectrum of phototaxis in zoospores of Pseudochorda sp.…”
Section: Introductionmentioning
confidence: 99%
“…In Polypodochrysis , the rhizoplast is associated with the non-flagellum-bearing basal body, and in some photosynthetic stramenopiles, such as Ochromonas , the rhizoplast is associated with the immature flagellum (Hibberd 1970;Bouck and Brown 1973;Andersen 1982). Also, the flagellum of Polypodochrysis did not contain a green autofluorescent material that is common in the mature flagellum of many photosynthetic stramenopiles (Kawai and Inouye 1989), including Phaeomonas (Honda and Inouye 2002). Furthermore, the typical R1 root in photosynthetic stramenopiles produces a number of cytoskeletal microtubules, but none of the microtubular roots of Polypodochrysis gave rise to secondary cytoskeletal microtubules.…”
Section: Discussionmentioning
confidence: 99%